ANALISIS PENGGUNAAN RASCH MODEL UNTUK VALIDITAS INSTRUMEN SELF EFFICACY PESERTA DIDIK DALAM PEMBELAJARAN MATEMATIKA - Rahmi. S, Laila; Rahayu, Wardani; Hidajat, Flavia Aurelia (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
This study aims to examine the validity and reliability of a self efficacy instrument in mathematics learning using the Rasch model. Self efficacy, which refers to an individual's belief in their ability to complete tasks, plays a crucial role in the learning process and problem-solving in mathematics. The methodology employed is a quantitative approach with a sample of 302 junior high school students in Tangerang City, selected through simple random sampling. The instrument consists of 36 statements covering 6 indicators of self efficacy, which were validated by mathematics teachers before distribution. Data analysis was conducted using Winstep software to produce consistent Rasch output. The results indicate that 30 out of 36 items in the instrument are valid and reliable, with a Cronbach’s alpha value of 0.88, indicating that the instrument has excellent reliability. These findings affirm that a valid and reliable self efficacy instrument can be used to identify students' needs and design appropriate interventions in mathematics learning.